1984
DOI: 10.1111/j.1768-322x.1984.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarity reversal of inside‐out thyroid follicles cultured within collagen gel: reexpression of specific functions

Abstract: Isolated porcine thyroid cells cultured in suspension in Eagle Minimum Essential Medium supplemented with calf serum (5-20%) reorganize to form vesicles, i.e. closed structures in which all cells have an inverted polarity as compared to that found in follicles: the apical membranes are bathed by the culture medium. Under these conditions, cells neither concentrate iodide nor respond to acute thyrotropin (TSH) stimulation. When embedded in collagen gel, these vesicles undergo polarity reversal to form follicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The hormone can therefore be added to the basal medium, thus making contact only with the baso¬ lateral side of the epithelial layer where TSH receptors, connected with the adenylate cyclase complex, are present (Chambard, Verrier, Gabrion & Mauchamp, 1983). Under these conditions, TSH desensitization of thyroglobulin exocytosis occurs with physiological concentrations of TSH (25 pU/ml), as previously observed with follicles embedded in collagen gels (Chambard, Verrier, Gabrion & Mauchamp, 1984). However, the continuous secre¬ tion of thyroglobulin under chronic TSH stimu¬ lation can, in part, be responsible for the weaker response to the further acute stimulation by decreas¬ ing the intracellular pool of secretory vesicles.…”
Section: Discussionmentioning
confidence: 84%
“…The hormone can therefore be added to the basal medium, thus making contact only with the baso¬ lateral side of the epithelial layer where TSH receptors, connected with the adenylate cyclase complex, are present (Chambard, Verrier, Gabrion & Mauchamp, 1983). Under these conditions, TSH desensitization of thyroglobulin exocytosis occurs with physiological concentrations of TSH (25 pU/ml), as previously observed with follicles embedded in collagen gels (Chambard, Verrier, Gabrion & Mauchamp, 1984). However, the continuous secre¬ tion of thyroglobulin under chronic TSH stimu¬ lation can, in part, be responsible for the weaker response to the further acute stimulation by decreas¬ ing the intracellular pool of secretory vesicles.…”
Section: Discussionmentioning
confidence: 84%
“…Iodination of thyroglobulin was not detected in the absence of TSH, but from 10 pU TSH/ml, iodide uptake and incorporation into thyroglobulin were maximal. In previous reports, the same TSH concen¬ tration was sufficient to allow iodide uptake and iodination by follicles embedded in collagen gel (Chambard, Verrier, Gabrion & Mauchamp, 1984) or FRTL-5 lines (Marcocci, Luini, Santisteban & Grollman, 1987). Other studies, using different culture systems, reported that TSH stimulated iodide uptake and its incorporation into thyroglobulin but that maxi¬ mal responses were often obtained with TSH concen¬ trations as high as 100 pU/ml (Mauchamp et al 1979) or 200 pU/ml (Fayet et al 1982).…”
Section: Discussionmentioning
confidence: 90%
“…4e). However, exposure of this surface to collagen provokes the formation of a lumen at the core of the follicle, reversion of polarity, and migration of the TJ in the plane of the lateral membrane until it occupies the innermost end of the intercellular space [4,5,26,27,104]. HCO3-secreting cells of the cortical collecting duct of the kidney possess CI-/HCO3 exchangers in the apical domain and proton pumps in the basolateral membrane.…”
Section: Polarized Proteins May In Turn Modify the Tjmentioning
confidence: 99%